2020
DOI: 10.1158/0008-5472.can-19-3066
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Chromosomal Architectural HMGB Proteins Could Be the Next Frontier in Cancer Therapy

Abstract: Chromatin-associated architectural proteins are part of a fundamental support system for cellular DNA-dependent processes and can maintain/modulate the efficiency of DNA replication, transcription, and DNA repair. Interestingly, prognostic outcomes of many cancer types have been linked with the expression levels of several of these architectural proteins. The High Mobility Group Box (HMGB) architectural protein family has been well studied in this regard. The differential expression levels of HMGB proteins and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 116 publications
2
18
0
Order By: Relevance
“…The latter explanation may also be true for etoposide-treated hESCs [ 25 ]. Higher telomerase activity in the etoposide-treated HMGB2 KD hESCs (relative to control treated cells) may confirm the reported involvement of HMGB proteins in the DNA damage response [ 6 ]. Thus, enhanced telomerase activation in etoposide-treated HMGB2 KD hESCs may reflect augmented DNA damage response in these cells due to the absence of HMGB2 as a DNA damage protective protein.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The latter explanation may also be true for etoposide-treated hESCs [ 25 ]. Higher telomerase activity in the etoposide-treated HMGB2 KD hESCs (relative to control treated cells) may confirm the reported involvement of HMGB proteins in the DNA damage response [ 6 ]. Thus, enhanced telomerase activation in etoposide-treated HMGB2 KD hESCs may reflect augmented DNA damage response in these cells due to the absence of HMGB2 as a DNA damage protective protein.…”
Section: Discussionsupporting
confidence: 68%
“…Our findings on the distinct roles of HMGB1 and HMGB2 in the modulation of telomerase activity in etoposide-treated cells could be of interest for developing strategies for augmenting the efficacy of anticancer drugs [ 6 ]. It remains to be established whether the reported distinct impact of HMGB KD on the efficacy of anticancer drugs ([ 6 ] and refs. therein and in this paper) is correlated with HMGB-dependent changes in the cellular activity of telomerase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of HMGB1 results in the instability of genome and leads to tumorigenesis. Thus, the roles of HMGB1 in regulation of DNA damage repair and cancer etiology indicate that targeting chromosomal architectural HMGB1 may provide a new perspective for cancer therapy [16]. HMGB1 located in the cytosol or mitochondria may bind to autophagy associated genes like Beclin 1 to regulate cell autophagy and mitophagy.…”
Section: The Dual Effects Of Hmgb1 In Cancermentioning
confidence: 99%
“…HMGB1 silencing was shown to inhibit autophagy and to increase asbestos-induced mesothelial cell death, thereby decreasing asbestos induced transformation ( 4 ) ( Figure 1 ). The importance of HMGB1 in cancerous transformation was also studied in a mouse mesothelioma model, where the investigators demonstrated that inhibition of HMGB1 binding to its receptors led to decreased tumor growth ( 5 , 6 ) again pointing out the importance of this mediator in MPM progression. In addition, serum concentrations of HMGB1 are also significantly higher in mesothelioma patients compared to healthy controls, indicating its significance in tumor development ( 7 ).…”
Section: Inflammatory Tumor Microenvironmentmentioning
confidence: 99%